Mild toxicity of polystyrene and polymethylmethacrylate microplastics in Paracentrotus lividus early life stages. (October 2020) - Thomas, Philippe J.; Oral, Rahime; Pagano, Giovanni; Tez, Serkan; Toscanesi, Maria; Ranieri, Pasquale; Trifuoggi, Marco; Lyons, Daniel M.
Abstract: The vast category of microplastics in the marine environment, encompassing among other aspects their persistence, degradation and impact on biota, has become an important topic of research. In spite of environmental health concerns, much work has yet to be done on understanding the potential roles of polymer sources, composition and particle sizes in causing adverse effects which have already been observed in a number of biota. The present study was aimed at adding to current knowledge by verifying if, and to what extent, embryogenesis in the sea urchin species Paracentrotus lividus is adversely affected by polystyrene and polymethylmethacrylate virgin microparticles over a size range 1–230 μm and at concentrations of 0.1–10 mg L −1 . Developing embryos which came in contact with the microplastics only after fertilisation did not display a significant increase of developmental defects. Unlike embryo exposures, when P. lividus sperm were exposed to the microplastics or their leachates, modest, yet significant effects were observed, both in terms of decreased fertilisation rate and increase of transmissible damage to offspring. Further, it was noted that larvae more readily ingested polymethylmethacrylate than polystyrene microparticles after 3 days which may represent a route for enhancing the toxicity of the former compared to the latter. Overall, these findings provide evidence for lesser sensitivity of P. lividus early life stages to microplastics compared to other urchins such as Sphaerechinus granularis . In turn, the more robust response of P. lividus highlights the importance of choosing an appropriate test species with the highest sensitivity when investigating mildly harmful materials. Highlights: Embryogenesis in urchin Paracentrotus lividus is adversely affected by microplastic. Polystyrene and polymethylmethacrylate decrease fertilisation rate of exposed sperm. Offspring show increased developmental defects suggesting transmissible damage. Polymethylmethacrylate more readily ingested by larvae than polystyrene. Paracentrotus lividus may be too robust for testing mild toxicity of microplastics.